Behind the Classroom Door: Uncovering Teacher Competence in the Kindergarten Learning Process - Junianti, Fitri; Sari, Mutia; Ranggayoni, Russy; Futhira, Nadia; Yusra, Yusra (Seulanga : Jurnal Pendidikan Anak, 2025)
This study aims to analyse teacher competence in the learning process at Sambinoe Kindergarten, Aceh Jaya District. The research used a descriptive qualitative approach with data collection techniques through interviews with three teachers as the main informants. The results showed that teachers have four main competencies, namely pedagogical, professional, social, and personality competencies. However, the application of these competencies has not been fully optimized. Pedagogical competence can be seen from teachers' understanding of children's characteristics and fun learning designs, but the use of learning media and the preparation of lesson plans are still very minimal so that learning becomes less effective and less interesting. Teachers' professional competence is supported by participation in training and seminars, although self-development still relies heavily on individual motivation. Social competence is reflected in teachers' ability to communicate with students, parents and the community, and to introduce local cultural values. Personality competence is reflected in teachers' efforts to be role models and maintain ethics. Overall, teachers' competencies, especially in lesson planning, media innovation and self-development, are improving.